2012
DOI: 10.3109/08820139.2012.736116
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of CD4+CD 25+ FOXP3+ T Regulatory Cell, Interferon-γ and Interleukin-16 in Malignant and Tuberculous Pleural Effusions

Abstract: The differential diagnosis between malignant and tuberculous exudative pleural effusions is an important clinical problem. The aim of current study is to evaluate the frequencies of T-regulatory cells (Treg) on the basis of distinct phenotypes in the differential diagnosis between malignant and tuberculous pleural effusion. In addition, to evaluate Interferon-gamma (IFN- γ) and interleukin-16 (IL-16) levels and their correlation to Treg cells in malignant and tuberculous pleural effusions. Sixty patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…In addition, the CD4 + CD25 + Foxp3 + Treg cells play an important role in controlling autoimmune reactions (Maggi et al, 2005;Xing et al, 2012), cell transplantation (Velaga et al, 2013), and infection immunity (Ibrahim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the CD4 + CD25 + Foxp3 + Treg cells play an important role in controlling autoimmune reactions (Maggi et al, 2005;Xing et al, 2012), cell transplantation (Velaga et al, 2013), and infection immunity (Ibrahim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators in large-scale studies have reported that lymphocytes play an important role in the pathogenesis of pleural effusion [14-17]. CD4 + T cells can be differentiated into interleukin 17 (IL-17)-producing T helper (Th17) cells.…”
Section: Introductionmentioning
confidence: 99%
“…Foxp3 (the forkhead/winged helix transcription factor) has a regulatory function in immunologic suppression and is correlated with the development of CD4 + CD25 + Treg cells (Aquino et al, 2013;Bruinsm et al, 2010;Ibrahim et al 2013). Wang et al (2008) have confirmed that cimetidine (CIM) serves as an adjuvant and suppresses the function of CD4 + CD25 + Treg cells, promotes both cellular and humoral responses and maintains homeostatic immunity in HBV DNA vaccine vaccinations (Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 85%